ANALISIS DAN EVALUASI MEKANISME PELAKSANAAN PEMBIAYAAN AL-MUSYARAKAH PADA BANK SYARIAH - Erni Susana (Jurnal Keuangan dan Perbankan, 2009)
Musyarakah is a cooperation between two parties or more to run a certain businesswhere each party gives fund and the profit and the risk will be took together as the agreementbefore. The process of analysis and evaluation (character analysis, ability analysis, financeanalysis, condition and business analysis, guarantee analysis) of musyarakah finance requestwas in writing by the initiator functionary. Depth of an analysis was adapted the complexitylevel of finance risk which was being considered. Document of analysis and finance evaluationwas the document consisting information and opinion. Initiator functionary was suggested toavoid a statement that was like a report or information from a customer only but he had tocheck the rightness.